Optimalisasi polri dalam menangani tindak pidana penipuan melalui media sosial di kepolisian Daerah Istimewa Yogyakarta - Aryuniwati Aryuniwati; Yanto Yanto (Kajian Hasil Penelitian Hukum, 2019)
Online fraud is basically a lot happening in the community, but only a few people who want to report it. In Polda DIY, in 2016 there were 6 cases handled, in 2017 there were 7 cases and in 2018 there were 4 cases. This study aims to determine and analyze the optimization of the National Police in handling fraud cases through social media and to find out and analyze the obstacles in handling fraud cases through social media. Data obtained from interviews and all other data, then analyzed with qualitative analysis methods to answer the problems that have been formulated, namely by analyzing the quality of the data obtained, in order to obtain a clear and relevant picture of criminal policy regarding the role of the police in tackling acts criminal fraud through the internet. The optimization of the National Police in handling fraud cases through social media has not been carried out optimally. This condition is caused by the inadequate capability of HRD personnel, both in terms of knowledge, skills, budget, facilities and targets. Where at present there is only one person who has participated in vocational education in the field of information technology so that the implications for investigators' skills are still low in the techniques and tactics of cyber crime disclosure. Constraints in handling fraud cases through social media, namely the budget owned by DIY Criminal Sub-Directorate of DIY Regional Police is still not fully sufficient for operational activities of investigations and criminal investigations including in uncovering cyber crimes, Sub Criminal Investigation V does not yet have infrastructure facilities to process Check Position data , Call Detail Record), and Short Masage Service, as well as the method of carrying out tasks are still hampered because of the bureaucratic process applied by the Criminal Investigation Police and related agencies side in terms of borrowing infrastructure facilities to process Position Check data, Call Detail Record, and Short Masage Service tends to take quite a long time.